Tropical Fruit Pests and Pollinators Biology, Economic Importance, Natural Enemies and Control - Pena, J.; Sharp, J.; Wysoki, M.; Ebooks Corporation (Wallingford : CABI, 2002)
Insect and other pests cause major economic damage on fruit crops in the tropics. However, some insects are beneficial. This book reviews these injurious and beneficial organisms and how they might be controlled to enhance fruit production and quality.
Contenido: Contributors; 1 Introduction; 2 Pests of Banana; Colour Plates; 3 Tropical Citrus Pests; 4 Pests and Pollinators of Mango; 5 Pests of Papaya; 6 Pests of Pineapple; 7 Pollinators and Pests of Annona Species; 8 Pests and Pollinators of Avocado; 9 Pests of Guava; 10 Pests of Minor Tropical Fruits; 11 Pests of Litchi and Longan; 12 Passion Fruit; 13 Quarantine Treatments for Pests of Tropical Fruits; Index
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: FRUTAS TROPICALES